2019
DOI: 10.3390/s19173783
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Open Source Ultrasound-Sensing Based Navigational Support for the Visually Impaired

Abstract: Nineteen million Americans have significant vision loss. Over 70% of these are not employed full-time, and more than a quarter live below the poverty line. Globally, there are 36 million blind people, but less than half use white canes or more costly commercial sensory substitutions. The quality of life for visually impaired people is hampered by the resultant lack of independence. To help alleviate these challenges this study reports on the development of a low-cost, open-source ultrasound-based navigational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
1
6
0
2
Order By: Relevance
“…The findings of this review highlight directions for future development and research. A major concern observed in our review was the size of the device, more specifically, the miniaturization of the device [7], [32], [44], [46], [48], [52], [61]. A similar concern was reported by Kuriakose et al [83], who reported a relationship between the device's size and its adoption.…”
Section: E Future Research Directionssupporting
confidence: 74%
See 3 more Smart Citations
“…The findings of this review highlight directions for future development and research. A major concern observed in our review was the size of the device, more specifically, the miniaturization of the device [7], [32], [44], [46], [48], [52], [61]. A similar concern was reported by Kuriakose et al [83], who reported a relationship between the device's size and its adoption.…”
Section: E Future Research Directionssupporting
confidence: 74%
“…Among sensor-based technologies, ultrasonic sensors were the most used in the included studies (n = 24). The use of ultrasonic sensors has demonstrated several benefits for mobility performance, including a decrease in navigation time [13], [36], [63], and detection of complex obstacles such as stairs [13], [36] and moving obstacles [7].…”
Section: Technologies 1) Obstacle Detection and Location Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, multiple researches have been carried out to help PVI in indoor navigation and identifying products in shops or other objects using Wi-Fi, Bluetooth, RFID, NFC, and tags. These solutions differ in the types of the signals used, the positioning method, and the accuracy [12][13][14][15][16][17][18][19]. These solutions fall into three categories: Tag Based Systems: Such as radio-frequency identification (RFID) and near field communication (NFC), which use wireless components to transfer data from a tag attached to an object for the purpose of automatic identification and tracking [20,21].…”
Section: Introductionmentioning
confidence: 99%